An Analysis of Public-Private Partnerships in East Africa - Tshombe, Lukamba Muhiya; Molokwane, Thekiso; Nduhura, Alex; Nuwagaba, Innocent (Research in World Economy, 2020)
The impact of the implementation of public-private partnerships (PPPs) in the Sub-Saharan African region on infrastructure and services is becoming increasingly perceptible. A considerable number of African countries have embraced PPPs as a mechanism to finance large projects due to a constrained fiscus. At present, many financial institutions, such as the World Bank, the International Monetary Fund and the African Development Bank, which finance some of the projects, have established a department or unit that mainly focuses on infrastructure development in developing countries. The private sector in Africa is equally seen as a significant partner in the development of infrastructure. African governments need to tap into private capital to invest in infrastructure projects. This scientific discussion provides an analysis of PPPs in the East African region. This article selected a number of countries to illustrate PPP projects in the sub-region. The analysis of this study illustrates that the East African region represents unique and valuable public-private partnership lessons in different countries. This study also traces the origins of PPPs to more than a century ago where developed countries completed some of their projects using the same arrangement. This paper further demonstrates that the application of PPPs is always characterised by three factors, namely a country, a sector and a project. Experts in the field often refer to these elements as layers, which usually precede any successful PPP.
Keywords: policy analysis; public-private partnerships; comparative; sector; Sub-Saharan Africa